2020
DOI: 10.3390/agronomy10040518
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Drought Stress Response Traits in Brachypodium spp.

Abstract: The root is the organ responsible for the uptake of water and therefore has a very important role in drought tolerance. The aims of the present work were to characterize nine traits of the root system architecture (RSA) and the shoot dry weight (W) of twelve genotypes of Brachypodium spp. under water stress and to establish the relationship between RSA phenotyping traits and SSRs. Two culture media, one standard (SM) and one (PEG) to induced water stress have been used. In SM medium, B. stacei had the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Two markers mapped on 1A and 2D were correlated with plant height, while spikelets/ spike was highly correlated to eight markers located on 6B, 2D, 2B, 5D, 1B and 4B Under drought-stress, (Mwadzingeni et al, 2017). González et al (2020) observed association between five root system architecture variables and SSR markers. Sallam et al (2019) stated that genotypes may be characterized as tolerant to drought at the germination or seedling stage, but these genotypes may be very sensitive to drought at the flowering stage.…”
Section: Discussionmentioning
confidence: 93%
“…Two markers mapped on 1A and 2D were correlated with plant height, while spikelets/ spike was highly correlated to eight markers located on 6B, 2D, 2B, 5D, 1B and 4B Under drought-stress, (Mwadzingeni et al, 2017). González et al (2020) observed association between five root system architecture variables and SSR markers. Sallam et al (2019) stated that genotypes may be characterized as tolerant to drought at the germination or seedling stage, but these genotypes may be very sensitive to drought at the flowering stage.…”
Section: Discussionmentioning
confidence: 93%